Contribution to petrogenesis of the Paleoproterozoic Basaltic Magmatism from the Araí continental rift, central Brazil. (October 2021) - Silva, Cleverton Correia; da Silva Souza, Valmir; Botelho, Nilson Francisquini; Dantas, Elton Luiz
Abstract: The Paleoproterozoic Araí continental rift, Central Brazil, hosts metabasaltic lava flows interbedded with a thick transgressive metasedimentary sequence at the basal portion of the Araí Group (Arraias Formation). The lava flows have basalt to basaltic andesite compositions, subalkaline, tholeiitic and within-plate geochemical signatures. These rocks still have low to moderate REEs content, negative Ta, Ti, Nb anomalies, higher La/Nb (2.69–5.06) and lower La/Ba (0.03–0.23) ratios, suggesting some degree of contamination. Isotopic geology data presented in this paper revealed zircon U–Pb crystallization age of 1783 ± 17 Ma, with a significant frequency of inherited zircon from Rhyacian (2221 ± 14 Ma), negative εNd (t) = −4.46 to −6.58, Nd TDM model age from 2.49 to 2.72 Ga and 87 Sr/ 86 Sr(i) = 0.702400–0.708293. The εNd(t) vs Nb/La and εNd(t) vs 87 Sr/ 86 Sr diagrams suggest low to moderate contamination rate, linked to interactions of the plume-derived magmas with the subcontinental lithospheric mantle and the Archean-Paleoproterozoic continental old-crust, during to ascent and intrusion episodes, respectively. These new data are nicely correlated with the available isotopic data (U–Pb, Sm–Nd, Sr–Sr) on the acid volcanic and A-type granites from the basal portion of the Araí rift, indicating an important bimodal magmatic event, with volcano-plutonic characteristics, occurred during the continental syn-rift stage. Highlights: First information/data on geochemistry and isotopic geology of the basaltic magmatism of the Araí Group.